Research on the Development of Oil Painting Cultural Creative Products based on Immersion Experience - Yongqiang Guo, (Design Engineering, 2020)
Immersive experience is a new business form formed by the integration of culture and science and technology, and it is also a frontier and growing new style in the field of cultural industry. It is a kind of experience activity which takes the space creation environment as the core format and relies on the digital quasi object; it allows the audience to enter the fictional world from the real experience, and conveys the creator's new interpretation and expression of self, everything, the world and the universe. This paper presents a computer-generated oil painting style video rendering algorithm. Taking the eigenvector value of the image structure tensor as the brush direction, the input video frame is drawn in multi-layer to effectively simulate the fluid feeling of oil painting; at the same time, an improved local lighting model is proposed, which can enhance the coating layer feeling of the video frame by using the bump mapping technology. In order to make the generated video frame have the color style of oil painting, the color features of the original oil painting are converted to the rendered video frame by using the color conversion method. The experimental results show that the algorithm can effectively generate the rendering video with Van Gogh style characteristics for a given input video. Thus, it integrates a large number of digital "quasi objects" of scientific and technological achievements and a large number of creative contents with modern aesthetic characteristics